When Knowledge Knows No Bounds - Atir, Stav; Rosenzweig, Emily; Dunning, David (Psychological Science, 2015)
People overestimate their knowledge, at times claiming knowledge of concepts, events, and people that do not exist and cannot be known, a phenomenon called overclaiming. What underlies assertions of such impossible knowledge? We found that people overclaim to the extent that they perceive their personal expertise favorably. Studies 1a and 1b showed that self-perceived financial knowledge positively predicts claiming knowledge of nonexistent financial concepts, independent of actual knowledge. Study 2 demonstrated that self-perceived knowledge within specific domains (e.g., biology) is associated specifically with overclaiming within those domains. In Study 3, warning participants that some of the concepts they saw were fictitious did not reduce the relationship between self-perceived knowledge and overclaiming, which suggests that this relationship is not driven by impression management. In Study 4, boosting self-perceived expertise in geography prompted assertions of familiarity with nonexistent places, which supports a causal role for self-perceived expertise in claiming impossible knowledge.